Water Quality Analysis of Nile Tilapia Hatchery Ponds at the Fish Hatchery Center in Tepas Sepakat Village, West Sumbawa Regency - Rahman, Abdul; Aulia, Jamiatul; Ulfa, Andi Maria; Hamzah, Amir; Apriani, Ari (Jurnal Pijar Mipa, 2025)
This research was conducted to evaluate the water quality of Nile tilapia (Oreochromis niloticus) hatchery ponds at the Fish Seed Center (Balai Benih Ikan, BBI) located in Tepas Sepakat Village, West Sumbawa Regency. Water quality is a critical factor that directly influences the success of aquaculture, particularly in hatchery operations where the survival and growth rates of fish fry are highly dependent on optimal environmental conditions. The study assessed key water quality parameters including temperature, dissolved oxygen (DO), pH, ammonia concentration, and water transparency. Measurements were carried out quantitatively through direct sampling from three hatchery ponds containing fry of different ages and sizes, with data collected over three consecutive days during morning and afternoon sessions. The results indicated that all measured parameters remained within the acceptable ranges established by the Indonesian National Standard (SNI 7550:2009) for freshwater aquaculture. Water temperature ranged between 25.9°C and 27.9°C, DO levels varied from 3.9 to 5.2 mg/L, pH values ranged from 7.5 to 8.2, ammonia concentration was consistently below 0.1 mg/L, and water clarity ranged from 40 to 46 cm. Although water clarity slightly exceeded the standard threshold, it was still within a tolerable range that could support sufficient light penetration for photosynthesis without posing risks to the aquatic ecosystem. These findings suggest that the water quality at the BBI Tepas Sepakat hatchery ponds is generally suitable for supporting healthy and productive tilapia breeding. However, continuous monitoring and adaptive water quality management, particularly concerning dissolved oxygen and light penetration, are recommended to maintain optimal rearing conditions and ensure long-term sustainability of the hatchery operations. These findings can serve as a useful reference in promoting sustainable aquaculture practices and can be used in aquaculture training programs to improve water quality management.